Reachable workspace reflects dynamometer-measured upper extremity strength in facioscapulohumeral muscular dystrophy - Han, Jay J.; De Bie, Evan; Nicorici, Alina; Abresch, Richard T.; Bajcsy, Ruzena; Kurillo, Gregorij (Muscle & nerve, 2015)
ABSTRACT Introduction: It is not known whether a reduction in reachable workspace closely reflects loss of upper extremity strength in facioscapulohumeral muscular dystrophy (FSHD). In this study we aimed to determine the relationship between reachable workspace and quantitative upper extremity strength measures. Methods: Maximal voluntary isometric contraction (MVIC) testing of bilateral elbow flexion and shoulder abduction by hand‐held dynamometry was performed on 26 FSHD and 27 control subjects. In addition, Kinect sensor‐based 3D reachable workspace relative surface areas (RSAs) were obtained. Loading (500‐g weight) effects on reachable workspace were also evaluated. Results: Quantitative upper extremity strength (MVIC of elbow flexion and shoulder abduction) correlated with Kinect‐acquired reachable workspace RSA (R = 0.477 for FSHD, P = 0.0003; R = 0.675 for the combined study cohort, P < 0.0001). Progressive reduction in RSA reflected worsening MVIC measures. Loading impacted the moderately weak individuals the most with additional reductions in RSA. Conclusions: Reachable workspace outcome measure is reflective of upper extremity strength impairment in FSHD. Muscle Nerve 52: 948–955, 2015